De milícias de Antigo Regime à milícia nacional: a formação da Guarda Nacional no Ceará (1831-1840) - Costa Júnior, José Airton Ferreira da (2016)
This study will examine the implications of the formation process of the National Guard and the consequent extinction of Militias and Ordinances. These last two forces had been created during the colonial period. Both colonies forces and the National Guard had in common the characteristic of being non-professional forces, or militia. However, the two colonial forces were organized from characteristic elements of the ancien regime societies, while the National Guard was organized by the values of the modern conception of citizenship adopted by the National States. This study is structured as follows: first place we seek to understand what were the main features of the militias and the motives for the states to adopt this kind of force; Secondly we will examine what were the reasons for the Empire of Brazil to extinguish the colonial militias and create in their place the National Guard; finally we seek to analyze the process of organizing the National Guard in the province of Ceara during the 1830s.